THE EFFECTS OF CERTAIN POLYPHENOLS ON AORTIC BLOOD VESSELS: EXPERIMENTAL AND CLINICAL ANALYSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Polyphenols, as bioactive compounds, have been widely studied for their cardiovascular protective effects. This study investigates the impact of specific polyphenols on the functional state of the aortic blood vessel, focusing on their potential role in modulating endothelial function, vascular tone, and oxidative stress. Experimental and clinical data were analyzed to determine the effects of polyphenols on vascular homeostasis, nitric oxide bioavailability, and inflammatory markers. The findings suggest that certain polyphenols may contribute to improved aortic elasticity and reduced vascular dysfunction, highlighting their potential therapeutic applications in cardiovascular disease prevention and management.